Lipid profile of bovine grade-1 blastocysts produced either in vivo or in vitro before and after slow freezing process - Sarah Janati Idrissi; Daniel Le Bourhis; Antoine Lefevre; Patrick Emond; Laurene Le Berre; Olivier Desnoës; Thierry Joly; Samuel Buff; Virginie Maillard; Laurent Schibler; Pascal Salvetti; Sebastien Elis (Scientific Reports, 2021)
Abstract Currently, in vitro embryo production (IVP) is successfully commercially applied in cattle. However, the high sensitivity of embryos to cryopreservation in comparison to in vivo (IVD) embryos slows the dissemination of this biotechnology. Reduced cryotolerance is frequently associated with lipid accumulation in the cytoplasm mainly due to in vitro culture conditions. The objective of this study was to evaluate the lipid composition of biopsied and sexed embryos, produced either in vivo or in vitro from the same Holstein heifers before and after a slow freezing protocol. Lipid extracts were analysed by liquid chromatography-high resolution mass spectrometry, which enabled the detection of 496 features. Our results highlighted a lipid enrichment of IVP embryos in triglycerides and oxidised glycerophospholipids and a reduced abundance in glycerophospholipids. The slow freezing process affected the lipid profiles of IVP and IVD embryos similarly. Lysophosphatidylcholine content was reduced when embryos were frozen/thawed. In conclusion, the embryonic lipid profile is impacted by IVP and slow freezing protocols but not by sex. Lysophosphatidylcholine seemed highly sensitive to cryopreservation and might contribute to explain the lower quality of frozen embryos. Further studies are required to improve embryo freezability by modulating the lipidome.